Obstacles Scientific Research in the Departments of Curriculum and Instructional Methods in Jordanian Universities from the of Perspectives Graduate Students - Al. Fayyoumi, Khalil A. Rahman; Al-Shogran, Rami Ibrahim (Dirasat: Educational Sciences, 2023)
Objectives: This study aimed at exploring the obstacles scientific research in the departments of curriculum and instructional methods in Jordanian universities. Methods: A questionnaire of 59 paragraphs was developed by the researcher to figure out the perspectives of graduate students. The questionnaire was distributed to five domains: working conditions, publishing procedures, research teams, research reviewers, and writing research. It was distributed on (71) of Graduate Students in five universities. Results: The study showed that the five areas confirmed the existence of obstacles facing graduate students in conducting scientific research to varying degrees, ranging from very high levels to low levels, and were arranged in descending order as follows: researchers, working conditions, publication procedures, research arbitration, writing research, and that the areas of scientific research obstacles vary according to the level of study (Master, Ph.D.), the number of and to publish it, more often than graduate students of the doctoral level face. Conclusion: The study recommended the importance of training graduate students (Masters and Ph. D.) in the Departments of curricula and teaching methods, on how to design scientific research, identify its problem and stages of implementation, statistical treatments, increase the issues of university educational journals, select arbitrators who adhere to the deadlines set in the arbitration of research, urge civil society institutions to provide financial and moral support for outstanding scientific research and work to employ the results of scientific research in economic development programs.